Methylation array signals are predictive of chronological age without bisulfite conversion - Hunter L. Porter; Victor A. Ansere; Ram Babu Undi; Walker Hoolehan; Cory B. Giles; Chase A. Brown; David Stanford; Mark M. Huycke; Willard M. Freeman; Jonathan D. Wren (GeroScience, 2025)
DNA methylation data has been used to make “epigenetic clocks” which attempt to measure chronological and biological aging. These models rely on data derived from bisulfite-based measurements, which exploit a semi-selective deamination and a genomic reference to determine methylation states. We found that non-methylation factors lead to “pseudomethylation” signals that are both confounding of epigenetic clocks and uniquely age predictive. We also failed to predict age using human genotyping arrays, but found that epigenetic clocks were overrepresented near genomic regions whose methylation state is dependent upon sequence variants. Quantifying these covariates in aging studies will be critical to building better clocks and designing appropriate studies of epigenetic aging.

Piloting wastewater-based surveillance of norovirus in England - David I. Walker; Jessica Witt; Wayne Rostant; Robert Burton; Vicki Davison; Jackie Ditchburn; Nicholas Evens; Reg Godwin; Jane Heywood; James A. Lowther; Nancy Peters; Jonathan Porter; et al. (Water Research, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

The Inhibition and Variability of Two Different RT-qPCR Assays Used for Quantifying SARS-CoV-2 RNA in Wastewater - George Scott; Nicholas Evens; Jonathan Porter; David I. Walker (Food and Environmental Virology, 2023)
Faecal shedding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its subsequent detection in wastewater turned the spotlight onto wastewater-based epidemiology (WBE) for monitoring the coronavirus-disease 2019 (COVID-19) pandemic. WBE for SARS-CoV-2 has been deployed in 70 countries, providing insights into disease prevalence, forecasting and the spatiotemporal tracking and emergence of SARS-CoV-2 variants. Wastewater, however, is a complex sample matrix containing numerous reverse transcription quantitative PCR (RT-qPCR) inhibitors whose concentration and diversity are influenced by factors including population size, surrounding industry and agriculture and climate. Such differences in the RT-qPCR inhibitor profile are likely to impact the quality of data produced by WBE and potentially produce erroneous results. To help determine the possible impact of RT-qPCR assay on data quality, two assays employed by different laboratories within the UK’s SARS-CoV-2 wastewater monitoring programme were assessed in the Cefas laboratory in Weymouth, UK. The assays were based on Fast Virus (FV) and qScript (qS) chemistries using the same primers and probes, but at different concentrations and under different cycling conditions. Bovine serum albumin and MgSO 4 were also added to the FV assay reaction mixture. Two-hundred and eighty-six samples were analysed, and an external control RNA (EC RNA)-based method was used to measure RT-qPCR inhibition. Compared with qS, FV showed a 40.5% reduction in mean inhibition and a 57.0% reduction in inter-sample inhibition variability. A 4.1-fold increase in SARS-CoV-2 quantification was seen for FV relative to qS; partially due (1.5-fold) to differences in reverse transcription efficiency and the use of a dsDNA standard. Analytical variability was reduced by 51.2% using FV while qS increased the number of SARS-CoV-2 negative samples by 2.6-fold. This study indicates the importance of thorough method optimisation for RT-qPCR-based WBE which should be performed using a selection of samples which are representative of the physiochemical properties of wastewater. Furthermore, RT-qPCR inhibition, analytical variability and reverse transcription efficiency should be key considerations during assay optimisation. A standardised framework for the optimisation and validation of WBE procedures should be formed including concessions for emergency response situations that would allow flexibility in the process to address the difficult balance between the urgency of providing data and the availability of resources.

Characteristics of fine and ultrafine aerosols in the London underground - Prashant Kumar; Juan C. Zavala-Reyes; Gopinath Kalaiarasan; Hisham Abubakar-Waziri; Gloria Young; Ian Mudway; Claire Dilliway; Ramzi Lakhdar; Sharon Mumby; Michał M. Kłosowski; Christopher C. Pain; Ian M. Adcock; et al. (Science of The Total Environment, 2023)

A spontaneous compound odontoma in an adult Sprague Dawley rat (Rattus norvegicus) - Keith Lewy; Mayane Faccin; Yogish Somayaji; Kamryn Pursell; Brian F Porter; Tracy H Vemulapalli; Jonathan Bova (Journal of Comparative Pathology, 2023)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Future winters present a complex energetic landscape of decreased costs and reduced risk for a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ) - Megan J. Fitzpatrick; Warren P. Porter; Jonathan N. Pauli; Michael R. Kearney; Michael Notaro; Benjamin Zuckerberg (Global Change Biology, 2020)
Winter climate warming is rapidly leading to changes in snow depth and soil temperatures across mid‐ and high‐latitude ecosystems, with important implications for survival and distribution of species that overwinter beneath the snow. Amphibians are a particularly vulnerable group to winter climate change because of the tight coupling between their body temperature and metabolic rate. Here, we used a mechanistic microclimate model coupled to an animal biophysics model to predict the spatially explicit effects of future climate change on the wintering energetics of a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ), across its distributional range in the eastern United States. Our below‐the‐snow microclimate simulations were driven by dynamically downscaled climate projections from a regional climate model coupled to a one‐dimensional model of the Laurentian Great Lakes. We found that warming soil temperatures and decreasing winter length have opposing effects on Wood Frog winter energy requirements, leading to geographically heterogeneous implications for Wood Frogs. While energy expenditures and peak body ice content were predicted to decline in Wood Frogs across most of our study region, we identified an area of heightened energetic risk in the northwestern part of the Great Lakes region where energy requirements were predicted to increase. Because Wood Frogs rely on body stores acquired in fall to fuel winter survival and spring breeding, increased winter energy requirements have the potential to impact local survival and reproduction. Given the geographically variable and intertwined drivers of future under‐snow conditions (e.g., declining snow depths, rising air temperatures, shortening winters), spatially explicit assessments of species energetics and risk will be important to understanding the vulnerability of subnivium‐adapted species.

Value of protected areas to avian persistence across 20 years of climate and land‐use change - Michelle A. Peach; Jonathan B. Cohen; Jacqueline L. Frair; Benjamin Zuckerberg; Patrick Sullivan; William F. Porter; Corey Lang (Conservation Biology, 2019)
Establishing protected areas, where human activities and land cover changes are restricted, is among the most widely used strategies for biodiversity conservation. This practice is based on the assumption that protected areas buffer species from processes that drive extinction. However, protected areas can maintain biodiversity in the face of climate change and subsequent shifts in distributions have been questioned. We evaluated the degree to which protected areas influenced colonization and extinction patterns of 97 avian species over 20 years in the northeastern United States. We fitted single‐visit dynamic occupancy models to data from Breeding Bird Atlases to quantify the magnitude of the effect of drivers of local colonization and extinction (e.g., climate, land cover, and amount of protected area) in heterogeneous landscapes that varied in the amount of area under protection. Colonization and extinction probabilities improved as the amount of protected area increased, but these effects were conditional on landscape context and species characteristics. In this forest‐dominated region, benefits of additional land protection were greatest when both forest cover in a grid square and amount of protected area in neighboring grid squares were low. Effects did not vary with species’ migratory habit or conservation status. Increasing the amounts of land protection benefitted the range margins species but not the core range species. The greatest improvements in colonization and extinction rates accrued for forest birds relative to open‐habitat or generalist species. Overall, protected areas stemmed extinction more than they promoted colonization. Our results indicate that land protection remains a viable conservation strategy despite changing habitat and climate, as protected areas both reduce the risk of local extinction and facilitate movement into new areas. Our findings suggest conservation in the face of climate change favors creation of new protected areas over enlarging existing ones as the optimal strategy to reduce extinction and provide stepping stones for the greatest number of species.

Applying species distribution modelling to a data poor, pelagic fish complex: the ocean sunfishes - Natasha D. Phillips; Neil Reid; Tierney Thys; Chris Harrod; Nicholas L. Payne; Cheryl A. Morgan; Hannah J. White; Siobhán Porter; Jonathan D.R. Houghton (Journal of Biogeography, 2017)
Aim Conservation management of vulnerable species requires detailed knowledge of their spatial and temporal distribution patterns. Within this context, species distribution modelling ( SDM ) can provide insights into the spatial ecology of rarely encountered species and is used here to explore the distribution pattern of ocean sunfishes ( Mola mola and M. ramsayi ). Both species are prone to high levels of bycatch and are classified respectively as Globally Vulnerable and Not Assessed by the IUCN ; although their overall range and drivers of distribution remain poorly defined. Here, we constructed suitable habitat models for Mola spp. on a global scale and considered how these change seasonally to provide a much needed baseline for future management. Location Global. Methods Sighting records collected between 2000 and 2015 were used to build SDM s and provided the first global overview of sunfish seasonal distribution. Post hoc analyses provided a quantitative assessment of seasonal changes in total range extent and latitudinal shifts in suitable habitat. Results Mola is a widely distributed genus; however, sightings exhibited significant spatial clustering most notably in coastal regions. SDM s suggested that Mola presence was strongly dependent on sea surface temperatures with highest probability of presence between 16 and 23°C. The models identified significant variation in seasonal range extent with latitudinal shifts throughout the year; although large areas of suitable year‐round habitat exist globally. Main conclusions We provided the first assessment of Mola distribution on a global scale, with evidence of a wide latitudinal range and significant clustering in localized “hotspots” (notably between 40–50°N). By assessing the results of SDM s alongside evidence from published satellite tagging studies, we suggest that the species within the genus Mola are highly mobile, acting as facultative seasonal migrants. By identifying key suitable habitat alongside potential movement paths, this study provides a baseline that can be used in active conservation management of the genus.

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

The epidemiology of triple-negative breast cancer, including race - Katrina F. Trivers; Mary Jo Lund; Peggy L. Porter; Jonathan M. Liff; Elaine W. Flagg; Ralph J. Coates; J. William Eley (Cancer Causes & Control, 2009)

Letter - Paul P. Smith; Porter P. Lowry; Jonathan Timberlake; Janice S. Golding (Conservation Biology, 2004)

Effects of centrally administered orexin-B and orexin-A: a role for orexin-1 receptors in orexin-B-induced hyperactivity - Declan N.C. Jones; Jane Gartlon; Frederick Parker; Stephen G. Taylor; Carol Routledge; Panida Hemmati; Richard P. Munton; Tracey E. Ashmeade; Jonathan P. Hatcher; Amanda Johns; Rod A. Porter; Jim J. Hagan; et al. (Psychopharmacology, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Yield, market quality and petiole nitrate concentration of non-irrigated Russet Burbank and Shepody potatoes in response to sidedressed nitrogen - Gregory A. Porter; Jonathan A. Sisson (American Journal of Potato Research, 1993)

Petiole nitrate content of Maine-grown Russet Burbank and Shepody potatoes in response to varying nitrogen rate - Gregory A. Porter; Jonathan A. Sisson (American Journal of Potato Research, 1991)